2017
DOI: 10.19082/4853
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perception of the strategies to gaining professional power: A qualitative study

Abstract: BackgroundPower in nursing is a broad concept that has a determining effect on the achievement of professional goals. Gaining power is essential for promoting the roles of nurses, improving their professional image and the consistent improvement of healthcare systems.ObjectivesThis study was conducted to identify and clarify strategies for gaining power in the nursing profession through the experiences of Iranian nurses.MethodsThe present qualitative grounded theory study was conducted on fifteen participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…This was related to the lack of autonomy of nursing as a legitimate career. In fact, lack of authority and autonomy has long been an obstacle preventing nursing from standing out as a full career [38,45]. There is a need for nursing scholars in China to work with those overseas to explore the boundary of nursing responsibilities and ways to gain authority and autonomy for nursing.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…This was related to the lack of autonomy of nursing as a legitimate career. In fact, lack of authority and autonomy has long been an obstacle preventing nursing from standing out as a full career [38,45]. There is a need for nursing scholars in China to work with those overseas to explore the boundary of nursing responsibilities and ways to gain authority and autonomy for nursing.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…No primeiro, as medidas de redução de custos, típicas em fases de crise, onde em particular os Enfermeiros são solicitados constantemente a fazer "mais com menos" (Robinson, 2012), encostando os Enfermeiros no limite da cidadania e da dignidade, mas que com a solidariedade e autonomia interpares, buscam incessante a procura de soluções para os problemas reais num conhecimento socialmente digno, coletivo e solidário. No segundo, obtendo a partilha de conhecimentos profissionais, métodos e habilidades entre pares, fortalecendo a solidariedade profissional, confiança, unidade, empatia, respeito e senso de poder, mais proficiente se numa equipa com uma atmosfera de solidariedade e confiança e apoiados na meritocracia (Sepasi, Borhani, & Abbaszadeh, 2017;Dan, et al, 2018).…”
Section: Conhecimento Solidáriounclassified
“…The performance of the role has been noted to have beneficial effects on patient outcomes by reducing medical errors (Choi et al, 2014). In addition, it helps nurses to achieve professional power and to enhance their selfconfidence (Sepasi et al, 2017). In Ghana, a nurse who advocates for patients is seen as a "Florence Nightingale" (Adu-Gyamfi et al, 2016), but the nurses are frequently faced with some challenges when performing this role.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the North America and Brazil have found that nurses often fail to succeed in their advocacy for patients because of this power imbalance; thus, they often remain silent and comply with medical directives rather than risk conflict with the physicians (Gerber, 2018;Tomaschewski-Barlem et al, 2016). Moreover, the historic submissiveness of nursing and its altruistic values have also become obstacles to patient advocacy and the professional empowerment of nurses today (Sepasi et al, 2017). Improving professional interactions and communication is important for gaining power in nursing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation